Infantile Periocular Capillary Hemangioma An Unusual Presentation - Karma L Bhutia; Amit Gupta (Delhi Journal of Ophthalmology)
A 22 days old infant presented with a large capillary hemangioma involving the right lower eyelid causing a total occlusion of the visual axis. The treatment given was a single intralesional triamcinolone acetonide injection (0.4 mg), followed a month later with systemic steroids (4mg) for 6 weeks. After 6 weeks, there was a significant reduction in the size of the mass resulting in clearing of the visual axis. We herein report a large infantile periocular capillary hemangioma which was successfully managed with a single injection of intralesional and systemic corticosteroids together.